YOGA ADOPTION INTENTIONS AMONGST UNIVERSITY STUDENTS: VARIABLES AND LINKAGES - Patil, Neha; Dubbala, Varshitha; Pote, Samiksha; Garimella, Sanjana; Yeravdekar, Rajiv; Singh, Ankit (Universitas Airlangga, 2024)
Introduction: Compared to earlier times, university students are showing low physical activity levels. Compared to university students in the USA, students at Indian higher education institutions are 30% less physically active. The habits and beliefs formed at this stage of life are expected to have a long-term influence. Yoga is considered an alternative therapy effective in improving physical and mental health. Assessing the factors influencing university students' yoga adoption intentions is essential. Aims: To evaluate the selected university students' physical activity level and the mediating role of cues to action. Methods: The research design is cross-sectional and causal. The response of 120 university students was collected. The analysis is based on Structural Equation Modelling (SEM), and the software used includes SmartPLS and Microsoft Excel. Results – The study confirms the full mediation role of cue to action on the relationship between positive attitude for yoga and behavioral intentions to adopt yoga (effect = 0.179, t = 3.098, p < 0.002). Similarly, cue to action partially mediates the relationship between friend's support for yoga and behavioral intentions to adopt yoga (effect = 0.102, t = 2.34, p < 0.019). Conclusion: The university administrators should increase the cue to action for adopting health promotion behavior, including yoga at all levels, i.e., individual, relationships, community, social and policy making. To begin with, interventions such as developing educational videos, mandatory health promotion courses, and a buddy system can be started.